A high-throughput assay for the identification of malarial transmission-blocking drugs and vaccines - Delves, M; Ramakrishnan, C; Blagborough, A; Leroy, D; Wells, T; Sinden, R (2012)
Following the cessation of the global malaria eradication initiative in the 1970s, the prime objective of malarial intervention has been to reduce morbidity and mortality. This motivated the development of high throughput assays to determine the impact of interventions on asexual bloodstage parasites. In response to the new eradication agenda, interrupting parasite transmission from the human to the mosquito has been recognised as an important and additional target for intervention. Current assays for Plasmodium mosquito stage development are very low throughput and resource intensive, and are therefore inappropriate for high throughput screening. Using an ookinete-specific GFP reporter strain of the rodent parasite Plasmodium berghei, it has been possible to develop and validate a high biological complexity, high throughput bioassay that can rapidly, reproducibly and accurately evaluate the effect of transmission-blocking drugs or vaccines on the ability of host-derived gametocytes to undergo the essential onward steps of gamete formation, fertilisation and ookinete maturation. This assay may greatly accelerate the development of malaria transmission-blocking interventions. © 2012 Australian Society for Parasitology Inc.